Clinical and Epidemiological Profile of Urethral Stricture Disease in Ogbomoso, Nigeria - Najeem A Idowu,; Peter O Odeyemi,; Olushola J Ajamu,; Ismail Oseni,; Ganiyu A Oyeniyi,; Adebayo A Adekunle,; Mumini W Rasheed,; Dhikrulah Adebayo,; Stephene I Adedokun, (AlQalam Journal of Medical and Applied Sciences, 2025)
Urethral stricture disease constitutes a major cause of bladder outlet obstruction in men. The clinical presentation of this pathology is not well understood in our community. Our objective was to discuss the clinical and epidemiological profile of this pathology. This was a hospital-based retrospective review of all cases of urethral stricture and urethral stenosis that were seen in our center between 2015 and 2024. Their case folders were retrieved from the hospital medical record department. Information on the clinical and epidemiological profile extracted was recorded in a designed proforma. Analysis was done by using the chi-square and Kruskal-Wallis test for categorical variables and Spearman’s correlation coefficient for continuous variables. A p-value of < 0.05 was considered statistically significant. A total number of 46 patients were managed for urethral stricture with a mean age of 37.7+/13.7SD within a range of 16-90 years and hospital period prevalence of 14 per 100,000. Stricture was noted to be common in the bulbar urethral (28, 60.9%), while the most common etiology was observed to be post-inflammatory. (25, 54.3) There was a significant association between location and etiology of the stricture (p-value< 0.001). The association between length and etiology of the stricture was also statistically significant (p-value<0.001). All the patients had a successful voiding trial at discharge. The most common cause of urethral stricture remains post-inflammation, and there was a significant association between location and etiology of stricture, as well as between length and etiology.